Does Brand Love Affect Brand Loyalty for Halal Product Consumers in Central Java? - Rola Nurul Fajria; Siti Hasanah; Suryani Sri Lestari; Sam'ani (Journal of Islamic Economics Lariba, 2022)
This study aims to analyze the relationship between brand love and brand loyalty of consumers of halal products in Central Java. The data were collected from 359 consumers of halal products. The SEM-PLS analysis was used to study the relationship between variables. All the proposed hypotheses were positively significant, except religiosity, which has not moderated the relationship between Brand Love and Brand Loyalty. This study confirms that brand love is significantly affected by brand trust, brand image, and brand experience. Also, Brand Love has a positive effect on Brand Loyalty. This study has contributed by exploring the intensity of brand love and its effect on Brand Loyalty in the halal product in Central Java, Indonesia. In addition, in terms of achieving brand image, which is the highest antecedent of love for the brand, it can be a consideration for marketers who offer halal products to potential consumers. Besides, that will also add to the existing knowledge about consumer-brand relationships in Central Java, Indonesia.